Development of Student Worksheet Based on POE (Predict-Observe-Explain) Model to Students Mathematical Problem Solving Skills - Fajar Falbiansyah (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This study aims to create student worksheet products based on the POE (Predict-Observe-Explain) model for student mathematical problem solving skills on quadrilateral topic that are valid, practical, and effective. This study uses the R&D method and the model used ADDIE. Validity is calculated based on the validation sheet. The average percentage obtained from material experts is 80% with a valid category, while the average percentage obtained from media experts is 81.33% with a very valid category. Practically is calculated based on response sheet. The average percentage obtained from students responses is 83.35% with a very practical category, while the average percentage obtained from teacher responses is 75.65% with a practical category, Effectiveness is calculated based on problem solving skills tests. Students who get a score that qualify the minimum completeness criteria is 75 will be considered complete. Amount of students who completed is 24 of 33 and got a completeness percentage 72.73% with an effective category so that the student worksheet can be used as teaching material.